Real-World Use of Bone-Modifying Agents in Metastatic Castration-Sensitive Prostate Cancer. (1st October 2021) - Mitchell, Aaron P; Mishra Meza, Akriti; Panageas, Katherine S; Lipitz-Snyderman, Allison; Bach, Peter B; Morris, Michael J
Abstract: Background: Bone-modifying agent (BMA) therapy is recommended for metastatic castration-resistant prostate cancer but not metastatic castration-sensitive prostate cancer (mCSPC). BMA treatment in mCSPC may therefore constitute overuse. Methods: In this retrospective cohort study using linked Surveillance, Epidemiology, and End Results–Medicare data, we included patients diagnosed with stage IV prostate adenocarcinoma from 2007 to 2015 who were 66 years of age or older at diagnosis and had received androgen-deprivation or antiandrogen therapy. We excluded patients who had previously received BMAs or had existing osteoporosis, osteopenia, hypercalcemia, or prior bone fracture. The primary outcome was receipt of BMA (zoledronic acid or denosumab) within 180 days of diagnosis (emergence of CRPC within this time frame is unlikely). The secondary outcome was receipt of a BMA within 90 days. Exposures of interest included practice location (physician office vs hospital outpatient) and the specialty (medical oncologist vs urologist) of the treating physician. Results: Our sample included 2627 patients, of whom 52.9% were treated by medical oncologists and 47.1% by urologists; 77.7% and 22.3% received care in physician office and hospital outpatient locations, respectively. Overall, 23.6% received a BMA within 180 days; 18.4% did within 90 days. BMA therapy was more common among patients treated by oncologists (odds ratio = 8.23, 95% confidence interval = 6.41 to 10.57) and in physician office locations (odds ratio = 1.33, 95% confidence interval = 1.06 to 1.69). Utilization has increased: 17.3% of patients received BMAs from 2007 to 2009 (17.3% zoledronic acid, 0% denosumab) and 28.1% from 2012 to 2015 (8.4% zoledronic acid, 20.3% denosumab). Conclusions: Among patients with mCSPC who had no evidence of high osteoporotic fracture risk, more than one-quarter have received BMAs in recent years. This overuse may lead to excess costs and toxicity.